Variation in levels of reactive oxygen species is explained by maternal identity, sex and body-size-corrected clutch size in a lizard. - Olsson, M; Wilson, M; Uller, T; Mott, B; Isaksson, C (2009)
Many organisms show differences between males and females in growth rate and crucial life history parameters, such as longevity. Considering this, we may expect levels of toxic metabolic by-products of the respiratory chain, such as reactive oxygen species (ROS), to vary with age and sex. Here, we analyse ROS levels in female Australian painted dragon lizards (Ctenophorus pictus) and their offspring using fluorescent probes and flow cytometry. Basal level of four ROS species (singlet oxygen, peroxynitrite, superoxide and H(2)O(2)) measured with a combined marker, and superoxide measured specifically, varied significantly among families but not between the sexes. When blood cells from offspring were chemically encouraged to accelerate the electron transport chain by mitochondrial uncoupling, net superoxide levels were three times higher in daughters than sons (resulting in levels outside of the normal ROS range) and varied among mothers depending on offspring sex (significant interaction between maternal identity and offspring sex). In offspring, there were depressive effects on ROS of size-controlled relative clutch size, which relies directly on circulating levels of vitellogenin, a confirmed antioxidant in some species. Thus, levels of reactive oxygen species varies among females, offspring and in relation to reproductive investment in a manner that makes its regulatory processes likely targets of selection.